EFFECT OF SUB-CHRONIC EXPOSURE TO CHROMIUM ON HAEMATOLOGICAL AND BIOCHEMICAL PARAMETERS OF MALE ALBINO RAT - Saha, Jahnabi; Choudhuri, Soma; Choudhuri, Dipayan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives : Exposure to chromium, the transition element found in many compounds of earth's crust, leads to various health hazards including cancer, dermatitis, damage of liver and kidneys and reproductive toxicity in both male and female. Toxic effect of chronic exposure to chromium at low environmentally relevant dose is recently recognized and less studied. In the present study, we evaluated the effect of sub-chronic exposure to low doses of chromium VI (K2Cr2O7) on various haematological and biochemical parameters in male albino rats. Methods : Male albino rats (160±10 gm) received 1/25, 1/50 and 1/100 of reported oral LD50 dose of chromium VI (K2Cr2O7) for 90 consecutive days. After treatment, the blood was collected for analysis of various haematological and biochemical parameters. Results : Exposure to chromium VI at 1/25 LD50 dose caused decrease in body weight gain and reduction in the weight of the reproductive organs along with increase in the weight of liver and kidney. Numbers of red blood cells, white blood cells, platelets and haemoglobin concentration reduced with increase in clotting time. The total sperm count and motility was also reduced in exposed rats. There was decrease in plasma protein and albumin concentration, with increase in plasma glucose and cholesterol level. The activity of enzyme alanine aminotransferase and enzyme aspertate aminotransferase was stimulated in treated rats. Conclusion : The results of the present study revealed that chronic low dose exposure to chromium VI resulted in a toxic effect in experimental male albino rats.